TEACHING READING BY USING PARAGRAPH SHRINKING STRATEGY - Ridianto Ridianto (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
The purpose of this research is to know whether Paragraph Shrinking Strategy gave or did not give significant effect on students’ reading ability. This research was an expemerintal research which is posttest-only control group design. The population of the research was Eight Graders of SMP N 2 Kec. Luak Payakumbuh. The sample was choosen by using cluster random sampling technique. The experimental class was treated by using Paragraph Shrinking Strategy while the control class was treated by using conventional strategy. The instrument of this research was reading test in multiplechoice form. This instrument was valid because it had content validity which had been taught before and it is sbased on the syllabus. Then, this instrument was reliable because the writer had done try out and split half reliability. Next, to analyze the data, the writer used the t-test formula that suggested by Gay to answer the hypothesis. It found that t-test (6.13) and t-table (2.021). It means that t-test was bigger than t-table. On the other word, Alternative Hypothesis (H1) was accepted and Null hypothesis (H0) was rejected. So, it can be concluded that Paragragraph Shrinking Strategy gave significant effect to teaching and learning process and can increase students’ reading ability.